S78 Lymphopaenia and increased ace levels stratify sarcoidosis patients to underlying increase in IFN-γ + lymphocyte and TNF-α+ monocytes respectively. (15th November 2016) - Kendrick, YK; Cole, SL; Hoyles, R; Ho, LP
Abstract : Introduction: Sarcoidosis is a heterogeneous disease, and different mechanisms may contribute to disease activity at any one time. Both TH1 lymphocyte (IFN-γ+, IL-2+ CD4 T cells) and activated tissue macrophages contribute to the formation of granuloma and are established disease pathways. More recently, monocytes (precursors of tissue macrophages) have also been implicated. We reasoned that if we could identify a commonly used clinical test as a biomarker for these disease pathways, it could be used as a disease activity marker, and to guide evaluation of new therapies and repositioning of current drugs. In this study, we question whether serum ACE and circulating lymphocyte count correlated with different cellular immune function. Methods: 44 consecutive patients fulfilling the ATS-WASOG diagnostic criteria for sarcoidosis within a 2-year period were recruited. Patients on treatment, current cigarette smokers, inter-current immune disease and malignancies were excluded. Blood samples from all patients were processed contemporaneously for ACE, lymphocyte counts and CD4 T cell intra-cellular cytokine staining (ICS) for IFN-γ, IL-2 and IL-17 and CD14hi monocytes ICS for TNF-α. Results and discussion: We found no correlation between lymphocyte count and ACE (r = −0.2; p = 0.86) suggesting that these two abnormalities reflected independent processes. Lymphopaenia was significantly correlated with markers of activated CD4 T cells (IFN-γ, IL2+ and TNF-α+) (r = −0.50, 0.50 and 0.60 respectively; all p < 0.001; Spearman Rank Sum test); while ACE only correlated with level of TNF-α+ monocytes (r = 0.60; p < 0.0001). Conclusions: These results suggest that high ACE and lymphopaenia (i) reflect disease activity (ii) are likely to be endpoints of two different mechanistic pathways, and (iii) that they could potentially stratify patients into those with lymphocytic dominant and monocyte dominant disease processes. Thus a monocyte pathway inhibitor could be used specifically in patients with high ACE levels while drugs that target T cell activity may be targeted to those with lymphopaenia.